Analysis of the Archard Linear Wear Model, a dynamic View of the Original Model - Ortiz Santiana, Kevin Alexander (2025)
The Archard model is a linear model that describes the wear of a sliding system1. However, if you want to apply this model to an oscillating system, some modifications must be considered and the use of differential equations can be a useful strategy. In an oscillating system, the contact surfaces perform repetitive back-and-forth movements. This can change the way wear occurs because surfaces can wear in different areas during each vibration cycle. Additionally, the applied load can change during the oscillation cycle, which can also affect wear.  To model this type of system, the use of ordinary or partial differential equations could be considered, depending on the complexity of the system. These equations will allow you to model how wear changes over time and how it depends on factors such as position and speed in the vibration cycle.